TRUMP’S STRATEGIES IN HIS SPEECH: A POLITENESS STRATEGIES APPROACH - Suswanto Ismadi Megah; Geledis Peronika Soframi (Universitas Riau Kepulauan, 2020)
This study was aimed to investigate politeness strategies of President Donald John Trump’s speech conducted on 21st January 2017 at Capitol Hill building in Washington DC. This study applied politeness theory of Brown and Levinson (1987) particularly positive and negative politeness strategies. The research data analyzed through a descriptive – qualitative method because the data was speech text. This study found 30 positive politeness strategies of the Donald John Trump’s speech text. While 1 negative politeness strategies data was only 1 data found. the other aim was to identify, the most frequency used of the strategy was strategy 10, found 9 times used (29%). This study concluded that Trump tended to use strategy 10 of positive politeness rather than the other strategies because he aimed to attract the audiences of the American people by promising something to the people that he wanted to make the audiences more happily in order the American people driven to vote for him in the Presidential election. Keywords: Positive, Negative Politeness Strategies, and Speech Text